2021
DOI: 10.1111/den.14197
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal carcinoma in achalasia patients managed with endoscopic submucosal dissection and peroral endoscopic myotomy: Japan Achalasia Multicenter Study

Abstract: Objectives Indications for peroral endoscopic myotomy (POEM) and endoscopic submucosal dissection (ESD) in patients with achalasia concomitant with esophageal carcinoma (EC) are unclear. This study aimed to clarify the role of POEM in cases of achalasia concomitant with EC and to elucidate the indications for ESD and efficient surveillance for EC. Methods We conducted a multicenter cohort study at 14 hospitals in Japan, including 3707 cases of achalasia‐related esophageal motility disorders (EMDs). Factors con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This study was conducted at 13 high-volume centers as part of a more retrospective cohort study of EMD cases, including achalasia (Japan Achalasia multicenter study; JAMS). 21 , 22 The study protocol was approved by the ethics committee of the respective institutions ( Supplementary Table 1 ). In JAMS, EMD cases diagnosed using standard methods, including HRM, esophagography, and esophagogastroscopy, and treated between 2010 and 2020 were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted at 13 high-volume centers as part of a more retrospective cohort study of EMD cases, including achalasia (Japan Achalasia multicenter study; JAMS). 21 , 22 The study protocol was approved by the ethics committee of the respective institutions ( Supplementary Table 1 ). In JAMS, EMD cases diagnosed using standard methods, including HRM, esophagography, and esophagogastroscopy, and treated between 2010 and 2020 were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…However, esophageal carcinoma is usually diagnosed at the advanced stage, because neoplasm symptoms are often hidden by the achalasia-induced dysphagia. Therefore, surveillance endoscopy is recommended for patients with achalasia, especially for patients with specific risks and a history of esophageal carcinoma[ 5 ]. Ohkura et al [ 6 ] reported that ESD for early esophageal carcinoma with achalasia is a safe and curative procedure, due to esophageal dilatation and wall thickening.…”
Section: Discussionmentioning
confidence: 99%
“…Ohkura et al [ 6 ] reported that ESD for early esophageal carcinoma with achalasia is a safe and curative procedure, due to esophageal dilatation and wall thickening. However, ESD on the POEM line is impaired by fibrosis[ 5 ]. Therefore, when compared to a staging operation, a one-off operation can reduce the risk of fibrosis-induced surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…T HIS MULTICENTER STUDY involving 14 highvolume centers was conducted as part of a larger retrospective cohort study (Japan Achalasia Multicenter Study, JAMS) in patients with EMDs including achalasia. 10,11 Patients diagnosed with EMDs using standard methods including HRM, esophagogram, and esophagogastroscopy and treated between 2010 and 2020 were enrolled in the JAMS.…”
Section: Patientsmentioning
confidence: 99%